The incineration of persons in jihad, criminal penalties and reprisals a critique of ISIS's argument in light of the sources - Haddad, Gibril Fouad 1960- (Islamic and Strategic Studies Institute Berhad, 2017)
On February 3, 2015 a video emerged online showing the young Jordanian airforce pilot Muath Al-Kasasbeh being burnt to death by "Islamic State of Iraq and Sham" affiliates (ISIS or IS). Another IS live burning video was released on December 22, 2016, this time of two Turkish prisoners of war. IS quoted the Syrian theologian Ibn Taymiyya in support of the licitness of the publicized burning alive of war captives as revenge and intimidation. The same argument was developed in prior and concurrent pro-IS literature and fatwas online and in print. This book shows that such as argument, fatwas, and act are in fact unislamic and have no basis whatsoever in the Qur'an, the authentic Sunna and acts of the Companions, or Islamic law in its totality, and that the burning of enemy captives, whether for retaliation, deterrence, or any other reason, is forbidden by consensus in the rulings pertaining to the conduct of war.